“Herbicidas postemergentes en el manejo de control de malezas y su efecto en el rendimiento del cultivo de arroz (Oryza sativa L.)” - Rocafuerte Ramos, Ángela Elizabeth (2019)
SUMMARY "Post-emergent herbicides in the management of weed control and its effect on the yield of rice (Oryza sativa L.)" The work consisted of gathering information from different sources of information on rice cultivation (Oryza sativa L.), since it is essential for the food of the world and national population, besides generating income it provides a source of work for the people who are in charge of Grow it Ecuador plants approximately 343 936 hectares, of which 332 988 are harvested, achieving a production of 1 239 269 t. In the province of Los Ríos approximately 114 545 hectares are sown, of which 110 386 hectares are harvested, reaching a production of 359 569 tons. The average yield of paddy rice with 20% moisture and 5% impurities was 3.92 t / ha. In conclusion, we can say that certain cases weeds are used for food and medicinal purposes, in addition certain weeds serve to prevent soil erosion and recycle mineral nutrients from the soil; however, several cultivable plants are determined as "undesirable" in areas where the crop is different and are therefore considered as weeds, which are a product of the alteration of natural vegetation, are undesirable plants and, possibly, constitute the most economic component. important of the total pest complex, which also includes insects, mites, vertebrates, nematodes and plant pathogens It is recommended to control weeds efficiently and avoid competition with the crop for water, light, nutrients and space, apply post-emergent herbicides in rice cultivation (Oryza sativa, L), in both seasons of sowing, and evaluate the incidence of weeds in crops, to avoid economic losses to producers. Keywords: Rice, weeds, post-emergent herbicides, yield.